The Feasibility Of Using Persian Garden Elements In Today’s Urban Areas Toward Social Interaction Enhancement - Khoshouie, Mohammad Rasoul; Alborzi, Fariba (The Turkish Online Journal of Design Art and Communication, 2016)
Nowadays in cities, the pale role and weak existence of human presence in urban spaces and its consequences as social evolutions is the most clear and definite mater than anytime. Cities in the history through their human scale, were place places for the people, given the widespread presence and growing tendency to the use of cars and the machinated life, gradually, the man replaced its place with car which, incidentally, is the product of himself. As a result of such conditions, have been gradually faded the interaction and reactions between citizens and the city, the outcome of such an event is common dejection and depression in today’s human societies. The need to return of people to the city and their role as active citizens are of the reasons of the existence of urban spaces. Squares, walkways and urban green spaces can be seen as the spaces that are able to meet the basic needs of people. Persian Garden is a phenomenon that over thousands of years, have played its role as a place for people. A lively and vibrant place where human through being in it, will step into a world different from their common environment. This article aims to evaluate the possibility of using the principles, elements and various systems of Persian Garden in urban green spaces so that in this way to be increased the desire of people for presence in these areas and positively affect social interaction and activities of people. Therefore, in the early sections, will be provided a brief introduction to the Persian Garden and then will be examined the various elements. In addition, at the end of the article, will be examined the terms of the use of the elements of Persian gardens in urban spaces.
Keywords: Persian Garden; Urban Space; Social Interactions